2023
DOI: 10.1186/s12912-023-01306-9
|View full text |Cite
|
Sign up to set email alerts
|

Current status and influencing factors of spiritual needs of patients with advanced cancer: a cross-sectional study

Abstract: Background Spiritual needs have been associated with better physical health outcomes and provide a context for patients to gain hope and significance in coping with disease. This study aimed to understand the status of spiritual needs of patients with advanced cancer and conducted a quantitative study on the relationship between patient-reported physical, psychological, and social influencing factors and spiritual needs based on a biopsychosocial-spiritual model. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The highest average score for Hope and peace was 3.61 ± 1.00. This is consistent with Shi et al (Shi et al, 2023) Previous studies are inconsistent, and this cross-sectional ndings suggest that patients with terminal cancer have a stronger need to express love and accept care from others. Although this study also found that patients with terminal cancer expressed a strong need for love and connection, such as "having a warm or caring person for me" (3.65 ± 1.20), participants in this study believed that it was more important to maintain hope for life, reduce their pain and achieve inner peace.…”
Section: Analysis Of the Current Spiritual Needs Of Patients With Ter...supporting
confidence: 92%
See 1 more Smart Citation
“…The highest average score for Hope and peace was 3.61 ± 1.00. This is consistent with Shi et al (Shi et al, 2023) Previous studies are inconsistent, and this cross-sectional ndings suggest that patients with terminal cancer have a stronger need to express love and accept care from others. Although this study also found that patients with terminal cancer expressed a strong need for love and connection, such as "having a warm or caring person for me" (3.65 ± 1.20), participants in this study believed that it was more important to maintain hope for life, reduce their pain and achieve inner peace.…”
Section: Analysis Of the Current Spiritual Needs Of Patients With Ter...supporting
confidence: 92%
“…This may be one reason why the pain degree cannot affect the overall spiritual needs of patients with terminal cancer in China. The study by Shi et al results found (Shi et al, 2023) that cancerrelated fatigue is the major factor affecting the spiritual needs of patients with terminal cancer. However, the results of this study did not nd a predictive effect of fatigue on spiritual needs, which may be due to other confounding factors or mediating variables between fatigue and spiritual needs.…”
Section: Factors In Uencing the Spiritual Needs In Patients With Term...mentioning
confidence: 99%
“…Studies (Kirca, et al, 2023)which also supported these findings underline that spiritual care of cancer patients decreases the physical problems, anxiety, sleep disorders, depression and disorders in their social functioning. Spiritual care can aid cancer patients connecting to self, and/or a higher power or nature, find meaning and purpose in life (Shi et al, 2023). Spiritual well-being in cancer patients can reduce symptoms of depression and increase life expectation (Nasution et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual intervention is considered as an important aspect of holistic care and has been identified as a standard component that contributes to the well-being of cancer patients. Therefore, spiritual interventions have been studied for their effects on anxiety and depression among patients with cancer (Shi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual needs are most commonly defined as the expectations and needs of each person to discover meaning, purpose and value in life (Shi et al, 2023). Cancer patients' spiritual needs not being met can harm their spiritual well-being (Damen et al, 2022;Pearce et al, 2012) and contribute to a lower quality of life and an increased desire for death (Goyarrola et al, 2023;Ripamonti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%